Influence of vitamin C feed supplementation on the growth, antioxidant activity, immune status, tissue histomorphology, and disease resistance in Nile tilapia, Oreochromis niloticus - Rowida E. Ibrahim (Aquaculture Reports, 2020)
The present study aimed to evaluate the influence of dietary incorporation of vitamin C (l-ascorbic acid phosphate) on the growth rate, antioxidant activity, certain immunological indices, and tissue histomorphology in Nile tilapia (Oreochromis niloticus L.) fingerlings. One hundred and eighty fingerlings (14.74 ± 0.016 g each) were randomly distributed into four groups based on basal diets supplemented with 0, 200, 300, and 400 mg kg–1 diet of vitamin C, respectively, for ten weeks. The dietary incorporation of vitamin C significantly increased the final body weight, total weight gain (TWG), specific growth rate, and daily weight gain (DWG) in all groups. The serum levels of vitamin C and growth hormone increased in the highest supplementation level group (400 mg kg–1). In a concentration-dependent manner, vitamin C markedly enhanced the serum and hepatic antioxidant activities, the levels of lysozyme, nitric oxide, and interleukin-10, the phagocytic percentage, and the relative percentage survival (RPS%) of the fish against Aeromonas sobria. The liver histoarchitecture was also improved in a level-dependent manner with vitamin C supplementation. In addition, intestinal histomorphology improved, as evidenced by the increase in villus height and width. Therefore, vitamin C could serve as a suitable dietary supplement for enhancing the growth, hepatic and intestinal structures, immune status, and resistance against A. sobria in Nile tilapia.